Petani Tembakau dalam Genduk sebagai Realitas Sosial: Tinjauan Sosiologi Sastra: Tobacco farmers in Genduk as a social reality: a review of sociology literature - Riswari, Aninditya Ardhana (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
This study was structured with the aim of analyzing the existence of tobacco farmers in Genduk as a social reality through a sociological review of literature. This study uses a qualitative descriptive research method that focuses on the sociology of literature approach through Wellek and Warren's sociology combined with the concept of social reality. The results of the study show that the tobacco farmers in Genduk are not mere works of fiction, but instead Genduk is the bearer of the